2016
DOI: 10.1016/j.cjtee.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the triceps tendon – A case series

Abstract: Triceps rupture is the least common among all tendon injuries. The usual mechanism of injury is a fall on an outstretched hand, although direct contact injuries have also been reported to cause this injury. The diagnosis of acute triceps tendon rupture may be missed, which can result in prolonged disability and delayed operative management. We presented three cases of acute triceps tendon rupture each at different site showing the spectrum of injury to the muscle and mechanism of injury and management were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Other local conditions which were reported to cause rupture include xanthoma, hemangiomendothelioma, injection of corticosteroids, attrition changes from degenerative arthritis and olecranon bursitis. 11,12…”
Section: Amentioning
confidence: 99%
“…Other local conditions which were reported to cause rupture include xanthoma, hemangiomendothelioma, injection of corticosteroids, attrition changes from degenerative arthritis and olecranon bursitis. 11,12…”
Section: Amentioning
confidence: 99%
“…Jaiswal et al [ 19 ] reported 3 cases about trans-osseous nonmetallic cerclage for repairing triceps tendon rupture (bone to tendon repair). In case 1 Ethibond (size 2) was used, in case 2 Ethibond (size 5) and in case 3 Ethibond (size 5).…”
Section: Tricepsmentioning
confidence: 99%
“…The postoperative protocol was the same among the cases: elbow immobilization in plaster for three weeks, triceps strengthening was started after three months and full triceps strength was reached after 1 year. In case 1 a 10 °terminal restriction of elbow flexion was established and in case 2 and 3 full triceps strength and range of motion was established [ 19 ].…”
Section: Tricepsmentioning
confidence: 99%
“…Triceps tendon rupture is also rare in humans 11 12 . Acute partial injuries are often managed conservatively but complete rupture is treated surgically, using transosseus tunnels, 11 followed by immobilisation in flexion 13 .…”
Section: Introductionmentioning
confidence: 99%